Analysis of Fire Risk Assessment in South Jakarta 2021 - Fauzia, Qanita; Lestari, Fatma; Wardani, Devi Partina (Jurnal ilmu kesehatan masyarakat (Online), 2022)
Jakarta is the capital city of Indonesia, with a dense population of more than 10 million population. DKI Jakarta Province is divided into five city areas, including South Jakarta. South Jakarta has an area of 141,17 km2, with more than three million population. The scope for this study focused on two sub-districts in South Jakarta, which are Pasar Minggu and Jagakarsa. The objective of this study was to provide fire risk situations in two sub-districts of South Jakarta. The study used a descriptive method with non-probabilistic sampling. Data collection was performed from June 2021 to July 2021 through focus group discussions (FGDs) and filling out questionnaires. FGDs were performed to the Local Government Fire Brigade, and questionnaires were filled out by the head of the RW. The FGD guideline and questionnaire were developed based on the fire risk assessment checklist. The checklist instrument was developed by utilizing a disaster fire risk approach, including fire hazard, vulnerability, and fire protection, with twenty-two questions. The data was then analyzed using univariate analysis, bar, and spider chart. The results showed three RWs with severe-risk classification. The factors that increase the risk of fire are the use of combustible building materials and the high density of population and buildings. There were several recommendations contributed such as firefighters must have a list of the high-risk areas and develop a rescue evacuation plan, doing a routine inspection in each target area, and raising public awareness for the community to increase participation in fire risk management.